Design and Validation of the Gender-Based Violence Stereotypical Beliefs Scale - Enrique Bonilla-Algovia; Andreea Gabriela Pana; Concepción Carrasco Carpio (Behavioral Sciences)
Gender-based violence is a public health issue influenced by culture and social values, which is why its comprehensive prevention requires addressing distorted beliefs and legitimising myths present in society. The aim of this study was, on the one hand, to design and validate the Gender-Based Violence Stereotypical Beliefs Scale (GBVSBS), and, on the other, to analyse the differences between men and women regarding these beliefs. The sample consisted of 404 university students from the Community of Madrid and Castilla-La Mancha (Spain), aged between 18 and 53 years. This study is based on a quantitative methodology and a cross-sectional design. The judgement of four specialists in the field supported the content validity of the items. Factorial analyses provided evidence for a two-factor model: myths about male perpetrators and myths about gender-based violence and female victims. The fit indices and reliability coefficients were adequate. Stereotypical beliefs about gender-based violence correlated with victim-blaming attitudes, and different levels of acceptance were found depending on gender. In conclusion, this study offers a valid and reliable instrument with which to analyse the sociocultural beliefs surrounding gender-based violence today, promoting the implementation of socio-educational interventions.